2018
DOI: 10.1093/ve/vey026
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous amdoparvovirus-related elements reveal insights into the biology and evolution of vertebrate parvoviruses

Abstract: Amdoparvoviruses (family Parvoviridae: genus Amdoparvovirus) infect carnivores, and are a major cause of morbidity and mortality in farmed animals. In this study, we systematically screened animal genomes to identify endogenous parvoviral elements (EPVs) disclosing a high degree of similarity to amdoparvoviruses, and investigated their genomic, phylogenetic and protein structural features. We report the first examples of full-length, amdoparvovirus-derived EPVs in the genome of the Transcaucasian mole vole (El… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…Therefore, it is feasible that similar mechanisms could be a factor affecting the role of AAV–EVE integrations, providing possible explanations for the conservation of dependoparval-EVEs through multiple speciation events within these lineages. For example, in the case of an EVE of amdoparvovirus origin identified within the Transcaucasian mole vole ( Ellobius lutescens ) genome, an intact NS gene fused with a bZIP transcription factor’s ORF ( Pénzes et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is feasible that similar mechanisms could be a factor affecting the role of AAV–EVE integrations, providing possible explanations for the conservation of dependoparval-EVEs through multiple speciation events within these lineages. For example, in the case of an EVE of amdoparvovirus origin identified within the Transcaucasian mole vole ( Ellobius lutescens ) genome, an intact NS gene fused with a bZIP transcription factor’s ORF ( Pénzes et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVEs can be derived from a variety of diverse viral families with RNA genomes, like retroviruses, or DNA genomes such as the Parvoviridae , which is composed of various genera including Ambidensovirus , Protoparvovirus , Amdoparvovirus , and Dependoparvovirus ( Belyi, Levine, and Skalka 2010 ; Katzourakis and Gifford 2010 ; Arriagada and Gifford 2014 ; Smith et al. 2016 ; Pénzes et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sequences derived from parvoviruses occur relatively frequently in animal genomes (13, 14, 17, 25, 26). However, these sequences overwhelmingly derive from a small proportion of parvovirus lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, these sequences overwhelmingly derive from a small proportion of parvovirus lineages. For example, ambidensovirus-derived EPVs dominate invertebrate genomes (14), whereas vertebrate EPVs almost exclusively derive from dependoparvoviruses, protoparvoviruses, or viruses closely related to these two genera (12, 13, 25, 26). In this study we found no trace of ChPV-derived sequences in tetrapod genomes, despite recent evidence that ChPVs infect this host group (21).…”
Section: Discussionmentioning
confidence: 99%
“…Amdoparvovirus and Protoparvovirus are monophyletic and both include viruses capable of infecting a wide range of carnivore hosts that, in some cases, overlap. However, they are separated by important genetic differences and the mechanisms behind "host-non-specificity" differ considerably between the two [18,37,65]. We may, therefore, expect significant differences in viral ecology and cross-species transmission dynamics for these two groups.…”
Section: Epidemiology and Ecology Of Parvoviruses And Their Hostsmentioning
confidence: 99%